Der hagiographische Topos Griechische Heiligenviten in mittelbyzantinischer Zeit - Pratsch, Thomas (Millennium-Studien / Millennium Studies, 2012)
This is the first systematic study of literary formulae (topoi) in Greek medieval lives of the saints. Thomas Pratsch compiles a comprehensive systematic catalogue of the topoi and in his evaluation of them provides new insights into the genesis, transmission and historical development of the genre of Greek saints` vitae.